(untitled) (Plant Tissue Culture and Biotechnology, 2016)
In vitro propagation of a rare orchid, Bulbophyllum nipondhii was carried out. Five different media were tested to find the suitable medium for seed germination and seedling development. The tangible results were obtained on VW medium. To assess the effect of pollination types on seed germination and seedlings development, seeds derived from different self?, cross? and open?pollination were examined. Open?pollinated seeds produced the best germination and the highest seedling development, followed by cross? and self? pollination. VW medium was supplemented with 0, 25, 50 or 75 g/l potato extract (PE) and 0, 50, 100, 150 or 200 ml/l coconut water (CW) to identify their most suitable concentration. PE (75 g/l) with 100 ml/l CW was found to be best combination. Plant Tissue Cult. & Biotech. 26(1): 37-46, 2016 (June)